Subcutaneous nodules caused by Pseudomonas aeruginosa: healing without incision and drainage - KORTEN, VOLKAN (My University, 1992)
In a patient with multiple myeloma, numerous indurated, subcutaneous nodules and pyomyositis due to Pseudomonas aeruginosa were noted. These lesions resolved with ciprofloxacin plus ceftazidime therapy without surgical incision and drainage. Despite another course of cancer chemotherapy after total disappearance, there were no recurrences at the end of 3 months. Quinolones initially combined with other antipseudomonal beta-lactam agents may be the drugs of choice in the management of patients with subcutaneous nodules caused by P. aeruginosa.
Keywords: Humans; Middle Aged; Male; Pseudomonas Infections; Skin Diseases, Bacterial; Multiple Myeloma; Fluconazole; Amikacin; Ceftazidime; Myositis